Stubby-Root Nematode, Paratrichodorus minor (Colbran) Siddiqi (Nematoda: Adenophorea: Triplonchida: Diphtherophorina: Trichodoridae: Trichodoridae) - William T. Crow (EDIS)
Nematodes in the family Trichodoridae (Thorne, 1935) Siddiqi, 1961, are commonly called "stubby-root" nematodes, because feeding by these nematodes can cause a stunted or "stubby" appearing root system. Paratrichodorus minor is the most common species of stubby-root nematode in Florida, and in tropical and sub-tropical regions worldwide. Paratrichodorus minor is important because of the direct damage it causes to plant roots, and also because it can transmit certain plant viruses. This document is EENY-339, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2004.